Length- and thickness-dependent optical response of liquid-exfoliated transition metal dichalcogenides - Synnatschke, Kevin; Cieslik, Patrick; Backes, Claudia (Chemistry of materials, 2019)
Because of their reduced dimensionality, two-dimensional materials show intriguing optical properties and strong light-matter interaction. In particular, group VI transition metal dichalcogenides have been extensively studied and proof-of-principle optical applications have been demonstrated. Most studies to date focus on individual mono- or bilayered micromechanically exfoliated samples, which often display significant variations between flakes. In this work, we study size-dependent optical properties of four group VI TMD materials: WS2, MoS2, WSe2, and MoSe2, each consisting of ensembles of nanosheets suspended in the liquid environment. Samples were produced by liquid-phase exfoliation and size-selected using cascade centrifugation with size and layer number distributions quantified by statistical atomic force microscopy. Differences in lateral size and layer number are reflected in systematic changes in the optical extinction and absorbance spectra, which we exploit to establish quantitative spectroscopic metrics to facilitate the measurement of nanosheet dimensions for each of the four materials. The lowest energy resonance, referred to as A-exciton, is analyzed in more detail. In all cases, an exponential red shift with increasing layer number is observed. Our experimental data, backed up with first-principle calculations, reveal that the magnitude of the shift is dependent on the molecular mass of the central metal atom (W, Mo), while the rate at which the peak shifts from monolayer to bulk depends on the band gap of the semiconductor.
Gesehen am 04.02.2020